The impact of COVID-19 on alternative and local food systems and the potential for the sustainability transition: Insights from 13 countries. - Nemes, Gusztáv; Chiffoleau, Yuna; Zollet, Simona; Benedek, Zsófia; Colantuono, Fedele; Dulsrud, Arne; Fiore, Mariantonietta; Holtkamp, Carolin; Tae-Yeon Kim; Korzun, Monika; Mesa-Manzano, Rafael; Reckinger, Rachel; et al. (Elsevier, 2021)
The COVID-19 pandemic has been a major stress test for the agri-food system. While most research has analysed the impact of the pandemic on mainstream food systems, this article examines how alternative and local food systems (ALFS) in 13 countries responded in the first months of the crisis. Using primary and secondary data and combining the Multi-Level Perspective with social innovation approaches, we highlight the innovations and adaptations that emerged in ALFS, and how these changes have created or supported the sustainability transition in production and consumption systems. In particular, we show how the combination of social and technological innovation, greater citizen involvement, and the increased interest of policy-makers and retailers have enabled ALFS to extend their scope and engage new actors in more sustainable practices. Finally, we make recommendations concerning how to support ALFS’ upscaling to embrace the opportunities arising from the crisis and strengthen the sustainability transition.